Adverse reactions of immune checkpoint inhibitors - E. R. Zagidullina; V. B. Kaliberdenko; E. R. Kulieva; V. S. Beter; T. S. Pronkina; V. A. Kushner; V. V. Taran (Медицинская иммунология, 2025)
Our objective was to consider the adverse reactions associated with usage of immune checkpoint inhibitors (ICI). The literature review includes a search for scientific papers from the databases PubMed, Embase, eLibrary, CyberLeninka and Web of Science, CNKI and MEDLINE by the following keywords: “immune checkpoint inhibitors”, “immune-mediated adverse events”, “immune checkpoints”, “antitumor therapy”, “immune system”, “side effects”. Over the past decade, the discovery of immune checkpoints followed by development of appropriate inhibitors have provided breakthrough advances in cancer treatment. The ICI-based therapy has opened a new era of antitumor treatment and has really improved clinical prognosis in the cancer patients. The antitumor effect of ICI is based on the blockade of CTLA-4 and PD-1/PD-L1 signaling pathways, thus promoting antitumor activity of lymphocytes. However, inhibition of immune checkpoints may also provoke dysregulation of immune responses and appearance of a new type of adverse reactions associated with changed activity of immunocompetent cells in the host organism, i.e., immunerelated side effects (irAEs). The most common side effects concern skin, hepatobiliary, and endocrine systems. Of note, the frequency of adverse events affecting cardiovascular and nervous systems is relatively low among total number of cases, but the consequences lead to disability of patients and are often fatal. Currently, hormonal drugs, immunosuppressants, and cytokine antagonists are mainly used to treat adverse events of ICI. However, these treatments may cause suppression of the immune system in patients, thereby weakening their antitumor immune response. There are still many unresolved issues related to irAEs, such as unclear mechanisms and biomarkers, tools for early detection of these adverse events, and development of more advanced individual treatments for such complications. The researchers believe that the above problems can be solved with wider use of immunotherapy, deeper studies on ICI and related adverse immune reactions, thus enabling full-scale implementation of ICI potential in anticancer therapy and improving clinical outcomes. Accordingly, the topic is quite relevant and requires close attention from practitioners and scientists.